ABUSE OF SOCIAL MEDIA FOR HATE SPEECH ACTION - Rosalia Dika Agustanti; Nuri Hidayati (Gorontalo Law Review, 2022)
The development of technology and information technology has resulted in freedom of opinion and expression which often leads to hate speech. So it is necessary to have clear limits on what actions can be classified as hate speech and to determine whether a person can be held criminally responsible. It is known that hate speech that often occurs is usually related to insults, defamation, blasphemy, unpleasant acts, provocations, and attempts to incite. The research method used is normative juridical with a statutory approach and a conceptual approach. The results show that the criminal responsibility of the perpetrators of hate speech has been regulated in several laws and regulations including the 1945 Constitution of the Republic of Indonesia, the Criminal Code, Law 9/1998, Human Rights Law, ITE Law, Law 40/2008, in addition to There is Circular Letter Number SE/6/X/2015 concerning Handling Hate Speech. There is no understanding about how to properly use social media to be one of the causes of hate speech, resulting in negative impacts. Social media which has been a place to communicate has changed its function. So that the issue of hate speech must be addressed intelligently by the community so that people are not easily instigated by hate speech that occurs. It is necessary to instill an understanding that hate speech will have a negative impact that can damage the life of the nation and state. For this reason, efforts to resolve hate speech can be done through penal and non-penal efforts. The police as the front line in handling and eradicating hate speech cases are assisted by the Ministry of Communication and Information of the Republic of Indonesia. As well as the importance of participation by fellow social media users to remind each other if one of them takes actions that lead to hate speech, as the saying goes, prevention is better than cure.